The effect of financial constraints on investment efficiency considering the size of companies (medium and small) - Mahnaz Ahangari; Mahdi Asadi Zarmehri (New Applied Studies in Management, Economics & Accounting, 2019)
The main purpose of this study is to investigate the effect of financial constraints on investment efficiency by considering the size of companies (medium and small). This research is empirical in terms of purpose. The statistical population of this study includes all companies listed on the Tehran Stock Exchange during the years 2011 to 2017. By modifying the population with conditions and by stratified random sampling, a statistical sample consisting of 130 companies were selected. Regression method has been used to investigate the type of relationship between variables and present a prediction model. In this statistical method, the relationship between variables is determined as a function of the dependent variable that predicts changes in the independent variable. The results also show a significant relationship between financial constraints as well as investment efficiency (more and less). The findings also showed that the moderating role of variable size of companies in the relationship between financial constraints and investment efficiency were confirmed.